Bushmeat and human health: assessing the evidence in tropical and sub-tropical forests - Vliet, N. van; Moreno, J.; Gómez, J.; Zhou, W.; Fa, J.E.; Golden, Christopher D.; Nobrega Alves, R.R.; Nasi, Robert (Universidade Estadual da Paraiba/Universidade Federal Rural de Pernambuco (Ethnobiology and Conservation), 2017)
The importance of bushmeat as source of food and medicine for forest peoples calls for an appropriate benefit/risk analysis in terms of human health. In this systematic review, we compiled information on the linkages between bushmeat and health, with a particular focus on the nutritional content, the zoo-therapeutic uses and the zoonotic pool of bushmeat species in tropical and sub-tropical forest regions. Despite the scarcity of data on the nutritional content of most common bushmeat species, the available studies demonstrate that bushmeat is an important source of fats, micro and macro-nutrients and has a diversity of medicinal uses. However, bushmeat may have detrimental health impacts where hunting, transportation, handling and cooking practices do not follow food safety practices. There is evidence that some bushmeat carcasses may be contaminated by toxic metals or by polycyclic aromatic hydrocarbons. Moreover, several pathogens carried by bushmeat are found to be zoonotic and potentially transmissible to humans through consumption or through exposure to body fluids and feces. We stress the need for more in-depth studies on the complex links between bushmeat and human health. The development of innovative handling, conservation and cooking practices should help reduce the negative impacts of bushmeat consumption on human health.